A Stochastic Integrated Inventory Model Single Supplier-Single Retailer in Periodic Review with Losing Flexibility Cost - Rizqi Afrizal; Utaminingsih Linarti (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
Efficiency in the supply chain can be established by integrating the supplier-retailer inventory policy. This article proposes the integrated inventory model between supplier-retailer under stochastic demand. This model aims to determine the optimal review period and calculate the total inventory cost, including some defective items, backorder price discounts, and losing flexibility costs. We assume that the retailer can order 'n' times for every 'm' shipment from supplier to retailer in each production cycle under a periodic review. Stochastic conditions can cause sudden changes in orders by the retailer in large quantities, eventually forcing the supplier to reduce their setup policies. This condition makes the retailer be charged a losing flexibility cost as compensation for the reduction setup pushed by the supplier in a long-term partnership contract. Based on numerical examples and sensitivity analysis, the percentage of defective items in each shipment from supplier to retailer significantly affects integrated total inventory cost.